2022
DOI: 10.1029/2022ja031013
|View full text |Cite
|
Sign up to set email alerts
|

Duct Effect of Magnetic Structures on Whistler Waves

Abstract: Whistler waves often have a right-hand polarization and a frequency below the electron gyrofrequency (f ce ) and are thought to be generated by suprathermal electrons with a temperature anisotropy (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Recent studies have found that not only density structures but also magnetic structures can affect the wave propagations (e.g., Yu & Yuan, 2022). MS waves have also been observed locally in magnetic structures without any leakage (Yu et al., 2022), suggesting potential ducting effects of MS waves through full reflections by the magnetic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that not only density structures but also magnetic structures can affect the wave propagations (e.g., Yu & Yuan, 2022). MS waves have also been observed locally in magnetic structures without any leakage (Yu et al., 2022), suggesting potential ducting effects of MS waves through full reflections by the magnetic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Then, one can solve the perpendicular refractive index (q) through Equations 3 and 4 with the observed wave frequency, plasma densities, and given values of p. EMIC waves can be retained in the magnetic dip for a long time if there exist closed loops in the solved q-patterns which indicates wave ducting via linear mode conversions, as has been demonstrated in Karpman and Kaufman (1982) and X. Yu and Yuan (2022).…”
Section: 1029/2022ja031178mentioning
confidence: 99%
“…Following previous studies (Karpman & Kaufman, 1982;Streltsov et al, 2006;X. Yu & Yuan, 2022), we will solve the refractive index inside the magnetic dip under certain plasma environments and find the potential mode conversions between branches with different refractive indices and Poynting vectors.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…Despite the abundant presence of magnetic structures in the inner magnetosphere, the trapping mechanism of the whistler‐mode waves by them has not been studied well. Recently, Yu and Yuan (2022) studied ducting of the whistler‐mode wave by the magnetic dips and peaks by analyzing the wave refractive index.…”
Section: Introductionmentioning
confidence: 99%